Expression and Function of IL12/23 Related Cytokine Subunits (p35, p40, and p19) in Giant-Cell Arteritis Lesions: Contribution of p40 to Th1- and Th17-Mediated Inflammatory Pathways - Espígol-Frigolé, Georgina; Planas-Rigol, Ester; Lozano, Ester; Corbera-Bellalta, Marc; Terrades-García, Nekane; Prieto-González, Sergio; García-Martínez, Ana; Hernández-Rodríguez, Jose; Grau, Josep M.; Cid, Maria C. (Frontiers in Immunology, 2018)
Background: Giant-cell arteritis (GCA) is considered a T helper (Th)1 and Th17-mediated disease. Interleukin (IL)-12 is a heterodimeric cytokine (p35/p40) involved in Th1 differentiation. When combining with p19 subunit, p40 compose IL-23, a powerful pro-inflammatory cytokine that maintains Th17 response. Objectives: The aims of this study were: to investigate p40, p35 and p19 subunit expression in GCA lesions and their combinations to conform different cytokines, to assess the effect of glucocorticoid treatment on subunit expression, and to explore functional roles of p40 by culturing temporal artery sections with a neutralizing anti-human IL-12/IL-23p40 antibody. Methods and Results: p40 and p19 mRNA concentrations measured by real-time RT-PCR were significantly higher in temporal arteries from 50 patients compared to 20 controls (4.35±4.06 vs 0.51±0.75; p < 0.0001 and 20.32±21.78 vs 4.17±4.43 relative units; p < 0.0001, respectively). No differences were found in constitutively expressed p35 mRNA. Contrarily, p40 and p19 mRNAs were decreased in temporal arteries from16 treated GCA patients versus those from 34 treatment-naïve GCA patients. Accordingly, dexamethasone reduced p40 and p19 expression in cultured arteries. Subunit associations to conform IL-12 and IL-23 were confirmed by proximity-ligation assay in GCA lesions. Immunofluorescence revealed widespread p19 and p35 expression by inflammatory cells, independent from p40. Blocking IL-12/IL-23p40 tended to reduce IFN and IL-17 mRNA production by cultured GCA arteries and tended to increase Th17 inducers IL-1 and IL-6. Conclusions: IL-12 and IL-23 heterodimers are increased in GCA lesions and decrease with glucocorticoid treatment. p19 and p35 subunits are much more abundant than p40, indicating an independent role for these subunits or their potential association with alternative subunits. The modest effect of IL-12/IL-23p40 neutralization may indicate compensation by redundant cytokines or cytokines resulting from alternative combinations.